Supramolecular aggregation patterns featuring Se⋯N secondary-bonding interactions in mono-nuclear selenium compounds: A comparison with their congeners - Tiekink, Edward R. T. * (Elsevier, 2021)
An evaluation of the Cambridge Structural Database for crystals containing Se…N secondary--bonding interactions was conducted. The presence of Se…N secondary-bonding interactions has been established in nearly 9% of crystals of mono-nuclear selenium compounds where such interactions can potentially form, that is, having at least one nitrogen atom. The Se…N interactions feature in 71 zero-dimensional, usually di-nuclear aggregates, 63 one-dimensional chains and tapes, and smaller numbers of two- and three-dimensional arrays, that is seven and one, respectively. Selenium(II) compounds form the majority of the dataset with only eight selenium(IV) compounds included in the survey. In most cases (112 out of 142), the selenium centre forms a single Se…N contact with 26 aggregates having a selenium atom forming two contacts and four examples where three Se…N contacts are evident. The great propensity of selenadiazole rings (75%) and selenocyanates (50%) to form Se…N secondary-bonding interactions in their crystals is particularly noteworthy.